2004
DOI: 10.1021/ed081p385
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Method for the Extraction and Thin-Layer Chromatography of Chlorophyll a and b from Spinach

Abstract: A direct method of extracting plant pigments from spinach leaves into a dry organic solvent is presented. A powder is obtained by grinding a mixture of raw spinach, drying agent, and sand (1:1:2) that can be extracted directly into acetone in 10 minutes to provide a sample suitable for chromatographic analysis. This method avoids liquid–liquid extractions and subsequent drying as is found in previously reported methods. Removal of the magnesium ion from chlorophyll pigments was observed by treating the acetone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 10 publications
(17 reference statements)
0
54
0
3
Order By: Relevance
“…These bands might correspond to pheophytinlike compounds that come from the partial degradation of chlorophyll a. Quach et al [27] reported that extraction methods with organic solvents that rely on high temperatures and/or prolonged periods of extraction result in some pigment degradation. Consequently, PLE caused a partial degradation of chlorophyll a because the loss of the magnesium ion from the chlorophyll ring resulted in the formation of the dark colored pheophytin at R f values higher than that of the original chlorophyll a. Ethanol was the solvent that caused the lowest formation of pheophytin, whereas the extraction with hexane and petroleum ether led to similar chlorophyll degradation.…”
Section: Analysis By Tlcmentioning
confidence: 99%
“…These bands might correspond to pheophytinlike compounds that come from the partial degradation of chlorophyll a. Quach et al [27] reported that extraction methods with organic solvents that rely on high temperatures and/or prolonged periods of extraction result in some pigment degradation. Consequently, PLE caused a partial degradation of chlorophyll a because the loss of the magnesium ion from the chlorophyll ring resulted in the formation of the dark colored pheophytin at R f values higher than that of the original chlorophyll a. Ethanol was the solvent that caused the lowest formation of pheophytin, whereas the extraction with hexane and petroleum ether led to similar chlorophyll degradation.…”
Section: Analysis By Tlcmentioning
confidence: 99%
“…The extraction of plant material such as green leaves is well known, e.g., [3,17,18]. Fresh spinach or rocket salad (ruccola) leaves were mixed with sand, some drying agent (e.g., magnesium sulfate), and acetone to just cover the leaves, then macerated in a mortar.…”
Section: Green Leaves Extractmentioning
confidence: 99%
“…7. When the developing solvent was loaded onto the sample spot, a yellow-orange component was first separated out, and a predominate peak corresponding to carotene ([M + H] + : m/z 537), a major pigment in spinach [43], could be detected (Fig. 7a).…”
Section: Characterization Of Different Components In Mixture Samplesmentioning
confidence: 99%
“…Following the separation and detection of the yellow carotene component, a grey-green component appeared to separate out and a major peak corresponding to pheophytin A ([M + H] + : m/z 871), another well known pigment in spinach [43], was observed (Fig. 7b).…”
Section: Characterization Of Different Components In Mixture Samplesmentioning
confidence: 99%